REDUKSI WASTE DENGAN PENERAPAN LEAN MANUFACTURING PADA PROSES PRODUKSI GLASSFIBRE REINFORCED CONCRETE (GRC) KRAWANGAN DI PABRIK XYZ - Ester Maria Elizabeth (Journal of Optimization System and Ergonomy Implementation, 2023)
The XYZ factory is a factory that produces GRC Krawangan products. From observations, there are inefficiencies caused by disorganized layout, irregular material handling, unnecessary movements, and waiting times. The identified waste can be analyzed for its causes and minimized to enhance production efficiency through Lean Manufacturing approaches. This research employs methods such as Value Stream Mapping (VSM), Value Stream Analysis Tool (VALSAT), Process Activity Mapping (PAM), Failure Mode Effect and Analysis (FMEA), and Fault Tree Analysis (FTA). The research results revealed a ranking of the 7 wastes, with the highest being waste in transportation, unnecessary motion, and waiting. These wastes were then assessed using VALSAT, and PAM emerged as the selected tool. Subsequently, FMEA data collection identified 7 sub-wastes exceeding Critical RPN. These sub-wastes were further analyzed using FTA. Based on the waste analysis through various methods, improvement proposals were made. These include enhancing facility layout with BLOCPLAN software, increasing the layout score from 0.72 to 0.99. The research also suggests the use of adjustable desk aids, successfully reducing the REBA score from 9 to 6. Additionally, in PAM, total activity improvement amounted to 129 by eliminating 9 activities, leading to a decrease in activity time from 98,862.69 to 97,495.72 seconds